(untitled) (Scientific journal of the Fergana State University, 2025)
The article philosophically analyzes gender relations and the phenomenon of an entrepreneurial woman in the process of social transformation of Uzbekistan. It is argued that the increase in women’s activism in society is important in ensuring an inextricable link between social stability, gender equality and economic progress. Public Policy and practical measures aimed at the development of women’s entrepreneurship, carried out in the country to ensure gender equality, are analyzed in harmony with international experiences. The article highlights the phenomenon of women entrepreneurs, their role in economic and social life, as well as the philosophical and cultural basis of this process. The analysis of foreign experiences enables the study of successful methods in achieving social equality and preventing economic crises by increasing the participation of women in economic activities. The experiences of foreign organizations, including the UN, UNDP and OECD, are important in the scientific improvement of programs to promote gender equality and support women’s entrepreneurship in Uzbekistan. The involvement of women in entrepreneurship not only accelerates economic development, but also serves to form new values in the social consciousness of society. The article will focus on the theoretical and practical aspects of this issue and promote proposals aimed at improving gender relations in Uzbekistan.